Massaging the Message: How Oilpatch Newspapers Censor the News - Blair Fix (Economics from the Top Down, 2023)
FROM THE ARTICLE. *** In their book Manufacturing Consent, Edward Herman and Noam Chomsky argue that the mainstream media functions largely as a propaganda arm for the state. When the war drum beats, the corporate media tows the government's line, censoring facts that don't fit the official narrative. *** Outside of war, media bias is typically less overt. But to the careful observer, it can still be discerned. In this case, our careful observer is Canadian oil critic Regan Boychuk. *** Boychuk lives in Calgary — a prairie city that is famous for two things. Calgary hosts the world's largest rodeo. And it is the corporate heart of the Canadian oil business. Calgary … home to cowboys and crude-oil CEOs. *** As you might guess, our story of media censorship is not about cowboys. Calgary's main newspaper, the Herald, is staunchly pro-oil. And that means its editorial pages are filled with oilpatch jingoism. However, the rest of the paper is an archetype of neutral reporting. Just kidding. *** Unsurprisingly, the Herald's pro-oil stance shapes the content that appears in the paper. This post takes a quantitative look at the editorial `curation'. *** Most of the heavy lifting has been done by Boychuk, who had the brilliant idea to track the reporting of environmental journalist Mike De Souza. Between November 2010 and July 2013, De Souza wrote a series of articles documenting scandals related to the Canadian oilpatch, and its staunch defender, the Harper government. *** At the time, De Souza was working for Postmedia, a news conglomerate that operated a wire service for its many subsidiaries. So when De Souza's pieces were published, they were delivered to local papers like the Ottawa Citizen, the Edmonton Journal, and the Calgary Herald. *** Here's the catch. Although owned by the same conglomerate, these local papers had leeway to edit (or shelve) their wire-service articles. The result, Boychuk realized, was a controlled setting to analyze media censorship. Earlier this year, Boychuk published his findings in a piece called `Proximity to Power: The oilpatch & Alberta's major dailies'. *** My contribution here is mostly visual. I've taken Boychuk's investigation and translated it into charts. The results largely speak for themselves. As De Souza's articles approached the center of Canadian oil-and-gas power in Calgary, they were increasingly gutted, and their message changed. It's a fascinating case study of how business interests shape the news.
Keywords: P; P1; P14; P18; L82; 330; Alberta; Canada; censorship; energy; environment; journalism; newspapers; oil